Sustainable innovation in ballistic vest design: Exploration of polyurethane-coated hemp fabrics and reinforced sandwich epoxy composites against 9 mm and .40 S&W bullets - WANTANG, Tannachart; PIPATHATTAKUL, Manop; WIWATWONGWANA, Fasai (Journal of Metals, Materials and Minerals, 2023)
This research aimed to evaluate the bulletproof capabilities of hemp fabrics and optimize the design factors for effective ballistic vests. Three main aspects were investigated: enhancing toughness with polyurethane-coated hemp fabrics, determining optimal placement of fabric-reinforced hemp epoxy composites in various configurations, and identifying the optimal number of fabric layers for performance against 9 mm and .40 S&W bullets. Penetration depth was measured in ballistic gelatin to analyze the results. The study showed strong statistical correlations between factor variables and penetration depth shifts. The most effective strategies included polyurethane-coated hemp on all layers and increased layering. The ammunition of 9 mm bullets exhibited the least penetration depth when tested against the sandwich-reinforced configuration. In contrast, the larger .40 S&W bullets demonstrated that the frontal arrangement yielded the minimum penetration depth. Notably, 9 mm bullets penetrated 1.25 times deeper than .40 S&W bullets. These findings emphasize hemp fabric’s potential for reliable ballistic vests. Utilizing polyurethane-coated hemp fabric in epoxy composites within a sandwich reinforcement of at least 212 layers is recommended to stop 9 mm bullets effectively. The research contributes valuable insights to sustainable ballistic vest development, utilizing natural materials with exceptional bullet protection capabilities.